Efeitos da pré-exposição ao etanol nos comportamentos relacionados à dependência desta substância e na expressão de CRF1 na amídala em ratos - Casula, Lígia Cury [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Ethanol addiction is a large public health problem, being a chronic disorder characterized by compulsive drug seeking and consumption. When access to ethanol is discontinued occurs withdrawal syndrome that is characterized by a set of unpleasant signs and symptoms. In rodents the ethanol withdrawal syndrome is evidenced by increased anxiety-like behaviors, changes in locomotor activity and intense drug seeking. It is known that the increased release of corticotropin-releasing factor (CRF) in various areas of the central nervous system including the amygdala is involved with the use of substances of abuse. In the present study we investigated whether exposure to ethanol in a liquid diet, followed by a short period of withdrawal, changes anxiety-like behaviors, locomotor activity, operant ethanol self-administration and levels of corticotropin releasing factor receptor type 1 (CRF1) in rats. For this purpose, adult male Wistar rats were pre-exposed to ethanol (6 a 8%) in a liquid diet with the food supplement Sustain®, as the only source of food or a liquid diet without ethanol over a period of 21 days intermittently. After this, the animals had quantified: 1) the ethanol withdrawal syndrome by measurement of anxiety-like behaviors in the elevated plus maze and locomotor activity in an automatic activity box, 2) CRF1 protein in the amygdala by Western Blotting or 3) motivation and consumption of ethanol in operant self-administration procedure. Our results demonstrate that pre-exposure to ethanol caused less motivation and lower consumption of this substance in the operant self-administration, but there were no changes in anxiety-like behaviors, locomotor activity or CRF1. Thus, these results suggest that prior exposure to ethanol causes a decrease of consumption and motivation for self-administration, and this change can be dissociated from the signs of withdrawal syndrome and changes of CRF1 receptor in the amygdala.

A dependência ao etanol é um grande problema de saúde pública, sendo uma desordem crônica caracterizada pela procura compulsiva e consumo abusivo desta substância. Quando o acesso à substância é interrompido ocorre a síndrome de abstinência que é caracterizada por um conjunto de sinais e sintomas desagradáveis. Em roedores a síndrome de abstinência ao etanol pode ser evidenciada pelo aumento de comportamentos relacionados à ansiedade, alterações da atividade locomotora e intensa procura pela substância psicoativa. Sabe-se que o aumento da liberação do fator liberador de corticotropina (CRF) em várias áreas do sistema nervoso central incluindo à amídala está envolvido com a utilização de substâncias de abuso. No presente estudo investigamos se a exposição a uma dieta líquida com etanol, seguida por um curto período de abstinência, altera comportamentos relacionados à ansiedade, atividade locomotora, autoadministração operante de etanol em ratos e os níveis do receptor fator liberador de corticotropina do tipo 1 (CRF1). Para tanto, ratos Wistar machos adultos foram pré-expostos a uma dieta líquida de etanol (6 a 8%) no complemento alimentar Sustain®, a qual foi oferecida como única fonte de alimento, ou receberam a dieta líquida sem etanol, durante um período de 21 dias de maneira intermitente. Após isso, os animais tiveram quantificado: 1) a síndrome de abstinência ao etanol pela mensuração dos comportamentos relacionados à ansiedade no labirinto em cruz elevado e a atividade locomotora em uma caixa automática de atividade, 2) a proteína CRF1 na amídala por Western Blotting ou 3) a motivação e consumo do etanol no procedimento de autoadministração operante. Nossos resultados demonstram que a pré-exposição ao etanol causou menor motivação e menor consumo dessa substância na autoadministração operante, mas não houve modificações nos comportamento
Keywords: Etanol; Alcoolismo; Neuropsicofarmacologia; Saúde pública; Ansiedade; Public health